Mental health service use: comparing people who served in the military or received Veterans' Affairs benefits and the general population - Annabel McGuire; Annette Dobson; Louise Mewton; Tracey Varker; David Forbes; Darryl Wade (Elsevier, 2015)
Abstract Objectives: To compare the lifetime prevalence of affective, anxiety and substance use disorders and the use of mental health services between people who had served in the Australian Defence Force (ADF) or received Department of Veterans' Affairs (DVA) benefits and the general population. Method: The 2007 National Survey of Mental Health and Wellbeing obtained data from a nationally representative household survey of 8,841 respondents. Results: Fewer than 20% of men who had served in the ADF reported receiving benefits from DVA. ADF men were older and more likely to report poorer health than other men. They were 50% more likely to be diagnosed with any lifetime mental disorder, any affective disorder, depression, PTSD, any substance use and alcohol disorder. Almost 90% of women who received DVA benefits had not served in the ADF. DVA women were older, and more likely to report moderate/severe psychological distress and less life satisfaction than other women. There was no evidence of greater lifetime use of mental health services by ADF men or DVA women compared to the general population. Conclusions: Health care providers should ask their patients if they have connections with the military in order to better detect and treat potential mental health problems.